2017
DOI: 10.1016/j.radonc.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Modality-specific target definition for laryngeal and hypopharyngeal cancer on FDG-PET, CT and MRI

Abstract: For laryngohypopharyngeal tumors, 45-52% target volume reduction compared with CTV is achievable when modality-specific CTV margins are used. PET-based CTVs were significantly smaller compared to CT- and MRI-based CTVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 26 publications
2
52
0
4
Order By: Relevance
“…When using DWI images, most observers found that there were indistinct boundaries at the edges of the delineation volumes. All observers felt a 5 mm expansion margin to CTV was appropriate which corresponds to the recommendations from the literature . Overall, observers found the DWI dataset useful or would consider its use in 50% of cases.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…When using DWI images, most observers found that there were indistinct boundaries at the edges of the delineation volumes. All observers felt a 5 mm expansion margin to CTV was appropriate which corresponds to the recommendations from the literature . Overall, observers found the DWI dataset useful or would consider its use in 50% of cases.…”
Section: Discussionsupporting
confidence: 63%
“…All observers felt a 5 mm expansion margin to CTV was appropriate which corresponds to the recommendations from the literature. 2 Overall, observers found the DWI dataset useful or would consider its use in 50% of cases. These 50% of cases were all oropharynx-based tumours (such as tonsillar tumours) as opposed to nasopharynx-based tumours.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations